Welcome to Westonci.ca, your ultimate destination for finding answers to a wide range of questions from experts. Experience the ease of finding reliable answers to your questions from a vast community of knowledgeable experts. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.

6p + 4 / 7 + 5p - 6 / 2 - 3p / 4 when p = 4

Sagot :

Step-by-step explanation:

Given p = 4,

substitute p= 4 into the expression

6p+4/7+5p-6/2-3p/4

[tex]6(4) + \frac{4}{7} + 5(4) - \frac{6}{2} - \frac{3(4)}{4} \\ = 24 + \frac{4}{7} + 20 - 3 - 3 \\ = 44 + \frac{4}{7} - 3 - 3 \\ = 38 + \frac{4}{7} \\ = 38 \frac{4}{7} [/tex]